What gives? Cross-national differences in students' giving behavior - Kang, C.; Handy, F.; Hustinx, L.; Cnaan, R.; Brudney, J.; Haski-Leventhal, D.; Holmes, Kirsten; Meijs, L.; Pessi, A.; Ranade, B.; Smith, K.; Yamauchi, N.; et al. (Pergamon, 2011)
This study is targeted to understanding the giving of time and money among a specific cohort ? university students across 13 countries. It explores predictors of different combinations of giving behaviors: only volunteering, only donating, neither, as compared to doing both. Among the predictors of these four types of giving behavior, we also account for cross-national differences across models of civil society. The findings show that students predominantly prefer to give money than to volunteer time. In addition, differences in civil society regimes provide insights into which type of giving behavior might dominate. As expected, in the Statist and Traditional models of civil society, students consistently weremore likely to be disengaged in giving behaviors (neither volunteering nor giving money) in comparison to students in the Liberal model who were more likely to report doing 'both' giving behaviors. An important implication of our findings is that while individual characteristics and values influence giving of time and money, these factors are played out in the context of civil society regimes, whose effects cannot be ignored. Our analysis has made a start in a new area of inquiry attempting to explain different giving behaviors using micro and macro level factors and raises several implications for future research.